IDENTITY OF BRANDS FOR BUILDING VISUAL NEUROCOMMUNICATION - Borisovna Yarosh , Olga; Alexandrovna Eremenko, Julia (Revista Inclusiones, 2020)
The development of new technologies and the introduction of innovations in branding are associated with the construction of a system of visual neurocommunication, formed on the basis of predictive analytics, including neurophysiological data. In order to isolate the neurometrics, two experiments were conducted. The first is aimed at assessing the visual visibility of a territorial identity in a competitive environment based on an analysis of ascending stimuli, namely, color and shape. The second experiment was aimed at studying the effect of visual stimulus (logo) on visual attention, interest and memorability. The oculomotor behavior of 36 test subjects was recorded in an array of 791 data sets.According to the results of data processing, eleven metrics have been proposed that can be used as a practical toolkit for managing customer attention in an information-rich competitive environment. As a result of the work it is shown that the visual visibility of logos depends on their color, shape and location. Complicated colors attract more attention, they have 25% more fixations, and the subjects show the strongest interest during color transitions and gradient fills, the number of fixations on similar objects is 70% higher.